Evaluation of intake of aged garlic extract and organosulfur compounds on progressive hearing loss in DBA/2J mice - Hideaki Oike; Kyoko Yamasaki; Kenji Hashiguchi; Honoka Uehira (PLoS ONE, 2025)
Garlic is rich in organosulfur compounds with high antioxidant capacity and is known to have various health benefits. Aged garlic is a particularly effective source of these active compounds because it contains fewer toxic components. This study evaluated the effects of S-allyl cysteine (SAC), a major functional organosulfur compound in garlic, and aged garlic extract (AGE) on the suppression of progressive hearing loss. SAC and AGE were dissolved in drinking water at 1% (w/w) and administered to DBA/2J mice, a model of early progressive hearing loss, for 12 weeks, starting at 4 weeks of age. While the results revealed a trend toward weight loss in the SAC group, the weight of the AGE group was comparable to that of the control group, and no adverse events were observed in either group. The hearing ability of the mice was measured using auditory brainstem responses at 4, 8, 12, and 16 weeks of age. Hearing loss at 8 and 16 kHz progressed over the 12-week period, with neither sample inhibiting hearing loss. In contrast, another organosulfur compound, N-acetylcysteine (NAC), administered in 1% w/w drinking water and evaluated for hearing loss over time, significantly suppressed hearing loss progression in DBA/2J mice. These results indicate that the NAC and SAC differ in their ability to prevent hearing loss and demonstrate that the inhibitory effects of functional food components on hearing loss can be evaluated over a short period in DBA/2J mice.